Konsep Protokol Kesehatan Wisata Edukasi Pada Daya Tarik Wisata Yayasan Tukad Bindu selama masa Pandemi Covid-19 - I Gusti Ngurah Pertu Agung; Ni Made Rai Kristina; I Gusti Ketut Indra Pranata Darma; Astrid Krisdayanthi; Ida Anuraga Nirmalayani (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2021)
Educational tourism as one of the development sectors of tourism is based on the community's need for educational variations. Educational tourism is suitable to be developed in locations that have limited locations and are in areas with residents. Tukad Bindu, as one of the densely populated areas in Denpasar, has the potential to develop educational tourism. The fast flow of the river becomes an attraction and strength in the tourism development needed by the local community. The learning model and the introduction of caring for nature can be applied to the tourist attraction of Tukad Bindu. In its development, the arrival of Covid-19 also affected the visit to the tourist attraction of Tukad Bindu which was seen in a drastic decrease in domestic tourists for almost 8 months. Strategic steps are needed in adapting the covid-19 virus so that the tourist attraction of Tukad Bindu can still run. This study aims to obtain a standard health protocol that can be done in entering the area of Tukad Bindu tourist attraction using a qualitative descriptive method. The results of the research can be used in application during the Covid-19 pandemic, so that people can still visit the tourist attraction of Tukad Bindu by following the applicable protocol.